Asset Securitization and Structured Financing : Future Prospects and Challenges for Countries in Emerging Markets - Alles, Lakshman (Washington, D.C. : International Monetary Fund, 2001)
This article examines the issues and challenges involved for institutions, policy makers, and law-makers in less developed countries in their efforts to implement asset securitization techniques in their financial markets. Challenges and issues in the areas of market development, legislation, accounting, regulation and structuring are examined in the light of recent developments in securitization techniques.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet